2016
DOI: 10.3390/molecules21040436
|View full text |Cite
|
Sign up to set email alerts
|

sym-Trisubstituted 1,3,5-Triazine Derivatives as Promising Organic Corrosion Inhibitors for Steel in Acidic Solution

Abstract: Abstract:Triazine derivatives, namely, 2,4,6-tris(quinolin-8-yloxy)-1,3,5-triazine (T3Q), N 2 ,N 4 ,N 6 -tris(pyridin-2-ylmethyl)-1,3,5-triazine-2,4,6-triamine (T3AMPy) and 2,2 1 ,2 11 -[(1,3,5-triazine-2,4,6-triyl)tris(azanediyl)] tris(ethan-1-ol) (T3EA) were synthesized and their inhibition of steel corrosion in hydrochloric acid solution was investigated using electrochemical techniques. The corrosion protection of the prepared compounds increased with increasing concentration and reached up to 98% at 250 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Compounds containing a quinoline core also showed anticorrosive activity in iron and steel in acidic solution [31] [32] [33]. Similarly, triazine derivatives presented anticorrosive activity in aluminum and steel in acidic me-Advances in Chemical Engineering and Science dium [34] [35] [36] [37]. In addition, compounds containing the morpholine group exhibited anticorrosive activity, mainly in steel, in acidic media [38] [39].…”
Section: Introductionmentioning
confidence: 96%
“…Compounds containing a quinoline core also showed anticorrosive activity in iron and steel in acidic solution [31] [32] [33]. Similarly, triazine derivatives presented anticorrosive activity in aluminum and steel in acidic me-Advances in Chemical Engineering and Science dium [34] [35] [36] [37]. In addition, compounds containing the morpholine group exhibited anticorrosive activity, mainly in steel, in acidic media [38] [39].…”
Section: Introductionmentioning
confidence: 96%
“…The presence of lone pair of electrons on nitrogen atoms, π‐electron on the phenyl ring, is the important structural features through which they can easily adsorb on the metal surface and bring down corrosion. A few triazine derivatives have been reported as corrosion inhibitors . A perusal of literature shows that there is no report on the use of triazines as corrosion inhibitors for N80 steel in 15% HCl.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported novel s -triazine derivatives as promising organic inhibitors (Figure 1) [27], and the reported results for electrochemical process revealed that, as the nitrogen content increased in the terminal chain, the effeciency for the corrosion protection of steel in acidic solution increased.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report easily prepared compounds with relatively low molecular weight and cheaper materials than the reported ones for triazine deriavtives [23,24,25,26,27] to stress the flexibility and the effect of the number of hydrazino groups along with the methoxy groups that directly attached to the triazine ring for corrosion inhibition of steel in acidic media.…”
Section: Introductionmentioning
confidence: 99%